2010
DOI: 10.1007/s10620-010-1361-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of EUS-FNA-Based Cytology in the Diagnosis of Mucinous Pancreatic Cystic Lesions: A Systematic Review and Meta-Analysis

Abstract: Background Preoperative diagnosis of malignancy in pancreatic cystic lesions (PCLs) remains challenging. Most non-mucinous cystic lesions (NMCLs) are benign, but mucinous cystic lesions (MCLs) are more likely to be premalignant or malignant. Aim The aim of this study was to assess the sensitivity, specificity, and positive and negative likelihood ratios (LRs) of EUS-FNA based cytology in differentiating MCLs from non-mucinous PCLs. Methods We conducted a comprehensive search of MEDLINE, SCOPUS, Cochrane, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 39 publications
6
96
1
4
Order By: Relevance
“…A meta-analysis [73] comparing EUS-FNA-based cytology with surgical biopsy or histology and including 376 patients from eleven [42,58,59,61,[74][75][76][77][78][79][80] studies showed a low sensitivity (63%), but good specificity (88%) in differentiating mucinous cystic lesions from non-mucinous lesions, with a diagnostic accuracy of 89%. However, the authors concluded that review literature on diagnostic accuracy of EUS-FNA-based cytology for pancreatic cystic lesions is limited and heterogeneous, and that welldesigned randomized trials are needed in this field.…”
Section: Eus-fnamentioning
confidence: 99%
“…A meta-analysis [73] comparing EUS-FNA-based cytology with surgical biopsy or histology and including 376 patients from eleven [42,58,59,61,[74][75][76][77][78][79][80] studies showed a low sensitivity (63%), but good specificity (88%) in differentiating mucinous cystic lesions from non-mucinous lesions, with a diagnostic accuracy of 89%. However, the authors concluded that review literature on diagnostic accuracy of EUS-FNA-based cytology for pancreatic cystic lesions is limited and heterogeneous, and that welldesigned randomized trials are needed in this field.…”
Section: Eus-fnamentioning
confidence: 99%
“…Therefore, a MCN will always be suspected when a medial-distal (corporeo-caudal) cystic lesion is identified in a middle-aged woman, the "mother" tumour, with no history of pancreatitis. Unlike SCN (serous cystic neoplasm), MCN are often malignant or they have a malignant potential (3).…”
Section: Mucinous Cystic Neoplasms (Mcn)mentioning
confidence: 99%
“…Despite best efforts, the sensitivity of cytology from EUS-FNA aspirates is in the range of 63% and specificity of 88% according to a meta-analysis by Thosani et al 21 There is a need for development and adoption of reliable surrogate cytological and molecular markers that can identify the type of pancreatic cyst and the degree of dysplasia.…”
Section: New Advances In Cyst Fluid Analysis By Tumor Markers and Molmentioning
confidence: 99%